2011
DOI: 10.2489/jswc.66.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Yield and water use response of winter wheat to winter irrigation in the North China Plain

Abstract: With intensifying water shortage, adoption of deficit irrigation strategies is likely to increase around the world. Winter wheat (Triticum aestivum L.) is one of the crops that has successfully been grown with deficit irrigation in the North China Plain. However, irrigating once before winter wheat enters dormancy (simplified as winter irrigation [WI]) is still a popular practice in this region. This study investigated the necessity of this irrigation and its effects on crop performance to provide guidelines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Our research confirmed that winter irrigation, especially drip irrigation with a large amount of water, created a good environment for the growth of jujube trees and improved the survival rate of young jujube trees. These results agree with those of Shao et al [13], Liu et al [9] and Chen et al [12], who found that winter irrigation created a good environment in the upper soil for crop growth. Moreover, Zhao et al [24] showed that winter irrigation can help maintain the soil moisture content and improve the rate of seedling emergence, especially irrigation with a relatively large amount of water.…”
Section: Discussionsupporting
confidence: 92%
“…Our research confirmed that winter irrigation, especially drip irrigation with a large amount of water, created a good environment for the growth of jujube trees and improved the survival rate of young jujube trees. These results agree with those of Shao et al [13], Liu et al [9] and Chen et al [12], who found that winter irrigation created a good environment in the upper soil for crop growth. Moreover, Zhao et al [24] showed that winter irrigation can help maintain the soil moisture content and improve the rate of seedling emergence, especially irrigation with a relatively large amount of water.…”
Section: Discussionsupporting
confidence: 92%
“…The slope for sufficient irrigation was low, in contrast to the high slopes for deficit irrigations. Similar to other studies (Jensen et al ., ; Shao et al ., ), this trend may indicate that wheat under deficit irrigation is more tolerant of water stress than under sufficient irrigation and is able to use water from the groundwater table more effectively. The relationship between Gc/ETa and groundwater table depth may be influenced by irrigation water or the amount of soil water depletion below the field capacity before irrigation, irrespective of the different watering regimes.…”
Section: Resultsmentioning
confidence: 97%
“…However, winter irrigation is still widely practiced in this region and is considered to compact the soil tillage layer for increasing the cold tolerances of winter wheat, particularly when straw from the previous crop is incorporated into the top soil. However, results from a previous study showed that the application of winter irrigation did not affect the growth and development of wheat in a normal season [31] . Winter irrigation increased soil evaporation during the long winter dormancy period and also increased water and nutrient leaching from the root zone which poses environmental risks.…”
Section: Further Developments In Deficit Irrigation Schedulingmentioning
confidence: 83%